High-throughput Selection of Human de novo-emerged sORFs with High Folding Potential - Aubel, Margaux; Buchel, Filip; Heames, Brennen; Jones, Alun; Honc, Ondrej; Bornberg-Bauer, Erich; Hlouchova, Klara (Genome biology and evolution, 2024)
De novo genes emerge from previously noncoding stretches of the genome. Their encoded de novo proteins are generally expected to be similar to random sequences and, accordingly, with no stable tertiary fold and high predicted disorder. However, structural properties of de novo proteins and whether they differ during the stages of emergence and fixation have not been studied in depth and rely heavily on predictions. Here we generated a library of short human putative de novo proteins of varying lengths and ages and sorted the candidates according to their structural compactness and disorder propensity. Using Förster resonance energy transfer combined with Fluorescence-activated cell sorting, we were able to screen the library for most compact protein structures, as well as most elongated and flexible structures. We find that compact de novo proteins are on average slightly shorter and contain lower predicted disorder than less compact ones. The predicted structures for most and least compact de novo proteins correspond to expectations in that they contain more secondary structure content or higher disorder content, respectively. Our experiments indicate that older de novo proteins have higher compactness and structural propensity compared with young ones. We discuss possible evolutionary scenarios and their implications underlying the age-dependencies of compactness and structural content of putative de novo proteins.
Keywords: genová knihovna; Gene Library; sbalování proteinů; lidé; Protein Folding; Protein Structure, Secondary; proteiny; sekundární struktura proteinů; Proteins; Humans